Chalaati Glacier variations in the past centuries, Georgian Caucasus, based on Dendrochronological and Beryllium-10 data - Levan G. Tielidze; Olga Solomina; Vincent Jomelli; Ekaterina Dolgova; Irina Bushueva; Vladimir Mikhalenko; Regis Braucher; ASTER Team (Лëд и снег, 2020)
Glacier variations over the past centuries are still poorly documented on the southern slope of the Greater Caucasus. In this paper, the change of Chalaati Glacier in the Georgian Caucasus from its maximum extent during the Little Ice Age has been studied. For the first time in the history of glaciological studies of the Georgian Caucasus, 10Be in situ Cosmic Ray Exposure (CRE) dating was applied. The age of moraines was determined by tree-ring analysis. Lichenometry was also used as a supplementary tool to determine the relative ages of glacial landforms. In addition, the large-scale topographical maps (1887, 1960) were used along with the satellite imagery - Corona, Landsat 5 TM, and Sentinel 2B. Repeated photographs were used to identify the glacier extent in the late 19th and early 20th centuries. 10Be CRE ages from the oldest lateral moraine of the Chalaati Glacier suggest that the onset of the Little Ice Age occurred ~0.74 - ~0.62 kyr ago (CE ~1280-1400), while the dendrochronology and lichenometry measurements show that the Chalaati Glacier reached its secondary maximum extent again about CE ~1810. Since that time to 2018 the glacier area decreased from 14.93±1.45 km2 to 9.89±0.50 km2 (33.75±7.4% or ~0.16 yr-1), while its length decreased by ~2280 m. The retreat rate was uneven: it peaked between 1940 and 1972 (~22.5 m yr-1), while the rate was slowest in 1910-1930 (~4.0 m yr-1). The terminus elevation rose from ~1620 m to ~1980 m in ~1810-2018.